PENGARUH JOB INSECURITY, LINGKUNGAN KERJA NON FISIK, DAN STRES KERJA TERHADAP KOMITMEN ORGANISASIONAL PADA KARYAWAN HOTEL ALPHA PEKANBARU - Qomariani Dewi Nurul; Garnasih Lestari Raden; Fitri Kurniawaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of Job Insecurity (X1), NonPhysical Work Environment (X2), and Job Stress (X3) on OrganizationalCommitment (Y) of Employees at Alpha Hotel Pekanbaru. The population of studywas 63 people and sampling technique used was saturation sampling (census).Primary data was collected by questionnaire as an instrument to prove the resultof the study, to test the hypothesis in this study using multiple linear regressionanalysis with the help of SPSS. The results showed that: 1) Job insecurity had anegative and significant effect on organizational commitment of employees atAlpha Hotel Pekanbaru; 2) Non physical work environment had a positive andsignificant effect on organizational commitment of employees at Alpha HotelPekanbaru; 3) Job stress had a negative and significant effect on organizationalcommitment of employees at Alpha Hotel Pekanbaru; 4) Job insecurity, nonphysical work environment, and job stress simultaneously effect on organizationalcommitment of employees at Alpha Hotel Pekanbaru. Keyword: Job Insecurity, Non Physical Work Environment, Job Stress,Organizational Commitment